Dynamics of paediatric urogenital schistosome infection, morbidity and treatment: a longitudinal study among preschool children in Zimbabwe. Issue 2 (27th March 2018) - Osakunor, Derick Nii Mensah; Mduluza, Takafira; Midzi, Nicholas; Chase-Topping, Margo; Mutsaka-Makuvaza, Masceline Jenipher; Chimponda, Theresa; Eyoh, Enwono; Mduluza, Tariro; Pfavayi, Lorraine Tsitsi; Wami, Welcome Mkululi; Amanfo, Seth Appiah; Murray, Janice; et al.
Abstract : Background: Recent research has shown that in schistosome-endemic areas preschool-aged children (PSAC), that is, ≤5 years, are at risk of infection. However, there exists a knowledge gap on the dynamics of infection and morbidity in this age group. In this study, we determined the incidence and dynamics of the first urogenital schistosome infections, morbidity and treatment in PSAC. Methods: Children (6 months to 5 years) were recruited and followed up for 12 months. Baseline demographics, anthropometric and parasitology data were collected from 1502 children. Urinary morbidity was assessed by haematuria and growth-related morbidity was assessed using standard WHO anthropometric indices. Children negative for Schistosoma haematobium infection were followed up quarterly to determine infection and morbidity incidence. Results: At baseline, the prevalence of S haematobium infection and microhaematuria was 8.5% and 8.6%, respectively. Based on different anthropometric indices, 2.2%–8.2% of children were malnourished, 10.1% underweight and 18.0% stunted. The fraction of morbidity attributable to schistosome infection was 92% for microhaematuria, 38% for stunting and malnutrition at 9%–34%, depending on indices used. S haematobium -positive children were at greater odds of presenting with microhaematuria (adjusted OR (AOR)=25.6; 95% CI 14.5 to 45.1) and stunting (AOR=1.7; 95% CI 1.1 to 2.7). Annual incidence of S haematobium infection and microhaematuria was 17.4% and 20.4%, respectively. Microhaematuria occurred within 3 months of first infection and resolved in a significant number of children, 12 weeks post-praziquantel treatment, from 42.3% to 10.3%; P<0.001. Conclusion: We demonstrated for the first time the incidence of schistosome infection in PSAC, along with microhaematuria, which appears within 3 months of first infection and resolves after praziquantel treatment. A proportion of stunting and malnutrition is attributable to S haematobium infection. The study adds scientific evidence to the calls for inclusion of PSAC in schistosome control programmes.